Biological and protein‐binding studies of newly synthesized polymer–cobalt(III) complexes. (17th August 2015) - Vignesh, G.; Pradeep, I.; Arunachalam, S.; Vignesh, S.; Arthur James, R.; Arun, R.; Premkumar, K.
Abstract: The polymer–cobalt(III) complexes, [Co(bpy)(dien)BPEI]Cl3  · 4H2 O (bpy = 2, 2′‐bipyridine, dien = diethylentriamine, BPEI = branched polyethyleneimine) were synthesized and characterized. The interaction of these complexes with human serum albumin (HSA) and bovine serum albumin (BSA) was investigated under physiological conditions using various physico‐chemical techniques. The results reveal that the fluorescence quenching of serum albumins by polymer–cobalt(III) complexes took place through static quenching. The binding of these complexes changed the molecular conformation of the protein considerably. The polymer–cobalt(III) complex with x = 0.365 shows antimicrobial activity against several human pathogens. This complex also induces cytotoxicity against MCF‐7 through apoptotic induction. However, further studies are needed to decipher the molecular mode of action of polymer–cobalt(III) complex and for its possible utilization in anticancer therapy. Copyright © 2015 John Wiley & Sons, Ltd.